Validation of inertial sensor to measure velocity of medicine balls - Sato, K.; Carroll, K. M.; Wagle, J. P.; Lang, H. M.; Smith, A. P.; Abbott, J. C.; Hierholzer, K. M.; Stone, M. H. (Journal of Trainology, 2018)
Objectives: The purpose of this study was to examine the validity of a wireless device measuring velocity via inertial sensor medi cine ball. Design and Methods: Sixteen healthy adults volunteered in the study. Each participant performed a series of three static and countermovement (CM) medicine ball chest throws. All throws were performed using 8-lb and 12-lb medicine balls inlayed with a wirelessly transmitted accelerometer and gyroscope. Reflective markers were placed on both sides of medicine ball and data were collected using a three-dimensional (3D) motion analysis system as the criterion measure. Pearson correlations and paired samples t-tests were calculated to assess the accuracy of the medicine ball peak velocity to that of the 3D motion analysis. Additionally, intraclass correlation coefficients (ICC) were calculated within each device to determine reliability. The alpha level was set as p = 0.05. Results: Pearson correlations indicated the medicine ball device to be relatively accurate with 3D motion analysis for static throws (r = 0.85-0.94) and CM throws (r = 0.62-0.89). There were no statistically significant differences between the two devices. ICC indicated trial-to-trial reliability of the medicine ball device to be acceptable (ICC = 0.74-0.98) compared to the 3D motion analysis (ICC = 0.67-0.98). Conclusion: Overall, the study demonstrated that relatively accurate data may be obtained from an inertial sensor medicine ball, indicated from the strong and very strong correlations with 3D motion analysis. Additionally, similar ICC values between the medicine ball and 3D motion analysis suggest the device yields acceptable reliability.